Tiny Homes Foundation. - Tiny Homes Foundation (Avalon Beach, NSW : Tiny Homes Foundation)
"Tiny Homes Foundation is a not for profit organisation dedicated to providing socially, environmentally and economically sustainable affordable housing solutions and support for people experiencing homelessness. The Tiny Homes Foundation pilot program will serve as a prototype for a new and innovative way to address Australia's growing affordable housing crisis though the development of Tiny Home villages in partnership with state and local government. The Pilot Program will comprise 4 to 6 tiny homes, a common space offering amenities and meeting facilities for the provision of welfare and education services.The project aims to work within a collaborative supported service model that seeks to address the needs of people experiencing and at risk of homelessness. We are an open source model to encourage other such projects across Australia, please check out our Projects page for more information. At Tiny Homes Foundation we believe we can make a difference one tiny home at a time."--About us.
Title from title screen (viewed on 22 August 2018)
Mode of access: Available Online. Address as at 27/08/2018
Selected for archiving
Keywords: Small houses -- Australia -- Design and construction; Sustainable architecture -- Australia; Australian